2006
DOI: 10.1074/jbc.m604046200
|View full text |Cite
|
Sign up to set email alerts
|

Underexpressed Coactivators PGC1α AND SRC1 Impair Hepatocyte Nuclear Factor 4α Function and Promote Dedifferentiation in Human Hepatoma Cells

Abstract: Hepatocyte nuclear factor 4␣ (HNF4␣) plays critical roles during liver development and in the transcriptional regulation of many hepatic genes in adult liver. Here we have demonstrated that in human hepatoma HepG2 cells, HNF4␣ is expressed at levels as high as in human liver but its activity on target genes is very low or absent. We have discovered that the low expression of key coactivators (PGC1␣, SRC1, SRC2, and PCAF) might account for the lack of function of HNF4␣ in HepG2 cells. Among them, PGC1␣ and SRC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 55 publications
3
40
1
2
Order By: Relevance
“…Because HSF1 is required for several processes that involve normal cell proliferation, such as spleen cell proliferation following immunization (40), muscle regeneration (41), and postnatal growth in C57BL/6 mice (42), it is possible that PGC-1α induction by fasting in liver (4) and muscle (43) represses HSF1 to mediate some of the antiproliferative effects of fasting. These scenarios also may hold true in cancer cells, although the potential effect of PGC-1α on cancer cell growth and survival is controversial, with reports suggesting both positive (44,45) and negative (46)(47)(48)(49)(50) associations between PGC-1α activity and cancer cell survival [including a negative association in HepG2 cells (51)], depending on the cellular context and on PGC-1α expression levels. It thus is possible that PGC-1α effects in cancer depend on a balance between its ability to induce metabolic genes and oxidative stress-response genes, a property that may promote cancer growth, and its ability to repress HSF1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Because HSF1 is required for several processes that involve normal cell proliferation, such as spleen cell proliferation following immunization (40), muscle regeneration (41), and postnatal growth in C57BL/6 mice (42), it is possible that PGC-1α induction by fasting in liver (4) and muscle (43) represses HSF1 to mediate some of the antiproliferative effects of fasting. These scenarios also may hold true in cancer cells, although the potential effect of PGC-1α on cancer cell growth and survival is controversial, with reports suggesting both positive (44,45) and negative (46)(47)(48)(49)(50) associations between PGC-1α activity and cancer cell survival [including a negative association in HepG2 cells (51)], depending on the cellular context and on PGC-1α expression levels. It thus is possible that PGC-1α effects in cancer depend on a balance between its ability to induce metabolic genes and oxidative stress-response genes, a property that may promote cancer growth, and its ability to repress HSF1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…HNF4α gene expression was also down-regulated by GTB, suggesting an association with the down-regulated gene expression of gluconeogenic enzymes. HNF4α is believed to be involved in protein kinase A's regulation of the G6Pase gene (6,19) and has a key role in regulating the PEPCK gene (9,14). Therefore, its down-regulation is expected to cause a decrease in G6Pase and PEPCK expression.…”
Section: Effects Of Fractions Derived From Gtb On Gene Expression In mentioning
confidence: 99%
“…This could result from an altered (mostly repressed) expression of liverenriched transcription factors and co-regulators. We have previously shown that this could be the case for C/EBP␣, HNF4␣, and CAR, three key transcription factors for the hepatic phenotype, which are down-regulated or dysfunctional in human HepG2 cells (16,17,21,27). The functional re-expression of these three factors in HepG2 cells has not only improved the critical pathways associated with a differentiated hepatic phenotype but also activated a number of drug metabolism and disposition enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the re-expression of the coactivator PGC1␣ in HepG2 cells enhances endogenous HNF4␣ activity on particular target genes (17). Consequently, we investigated whether PGC1␣, by coactivating endogenous HNF4␣, is able to improve CYP2B6 expression in cooperation with CAR and C/EBP␣.…”
Section: Discussionmentioning
confidence: 99%